Klasifikasi Tingkat Retensi Pemain Video Game Online - Mustofa Mustofa; Heru Purwanto; Fabriyan Fandi Dwi Imaniawan (Informatics and Computer Engineering Journal, 2024)
The internet has become an integral part of people's lives, with 5.44 billion users worldwide and 185 million users in Indonesia. Internet use covers a wide range of areas, including entertainment such as video games, which had an estimated 3.38 billion global users in 2023 and continues to grow. The video game industry shows huge market potential, with significant revenues. To exploit this potential, game developers must maintain player loyalty. Player retention, i.e. a game's ability to retain players over a long period of time, is critical in increasing a game's revenue and popularity. Knowing player retention rates is a key strategy in marketing, as high retention is associated with higher loyalty. Previous research has examined player behavior and retention in the context of games, but there is no comprehensive model for various types of games. This research aims to develop a classification model that can identify the characteristics of players with high or low retention rates. This model is expected to help game developers design more effective retention strategies. The findings of this research will provide in-depth insight into the factors that influence player retention and offer guidance for game developers in developing better features and strategies to retain players.